ANALISIS PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP MOTIVASI BERPRESTASI MAHASISWA DI MATA KULIAH KESEKRETARIATAN DENGAN KONSEP DIRI SEBAGAI VARIABEL MEDIASI PADA MAHASISWA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI MADIUN - Lisdiantini, Netty; Mirza Syafitri, Eva; Kusumawardani, Media (Widya Warta, 2017)
The objective of the research was to figure out the impact of interpersonal communication relationship on the student acievement motivation with the self-concept as the mediating variable. This research examined the direct effect of self-concept on the student achievement motivation, the direct effect of interpersonal communication on the student achievement motivation, and the indirect effect of interpersonal communication on the student achievement motivation. The object of the research was the 3rd semester students of Business Administration study program, State Polytechnic of Madiun in 2015. The data of the research were based on the number of population. The data used were primary and secondary data. The data were analized using multiple regression with SPSS. This research indicated that the interpersonal communication had direct effect on the self-concept. This self-concept directly affected the student achievement motivation. The result of this research also indicated that the interpersonal communication only indirectly affected the student achievement motivation through the self-concept.